Mechanistic insights into nano-regional heterostructures for photocatalytic and photoelectrochemical applications - Feng, Han (Nanyang Technological University, 2020)
Heterostructures with rationally designed junctions have been studied and applied in many emerging applications ranging from solar cells, photodetectors to photo/electro-catalysis. In the development of photocatalysts with superior performances for clean energy generation and decontamination of organic pollutants, heterostructures constructed with different semiconductor components are highly preferable due to their programmable optical and electrical properties, such as the widened response to incident wavelenth which can even reach the near-infrared (NIR) region and effective separation of photoinduced excitons for prolonged lifetime of reactive sites. However, there is a lack of understanding of nanoscale interfacial conditions, especially the interplay between nanosensitizer morphologies and charge carrier kinetics is still debatable. Thus, this dissertation aimed to explore possible working mechanisms of nanoscale semiconductor mediated heterostructures in photocatalytic and photoelectrocatalytic processes. Nano-regional heterostructures composed of nanosensitizers and classic semiconductor matrixes were designed and synthesized through hydrothermal and chemical precipitation methods. Scanning electron microscopy and high-resolution transmission electron microscopy were used to examine the morphologies, while X-ray diffraction and X-ray photoelectron spectroscopy were employed to determine the crystalline properties and elemental status of the synthesized materials. UV-Visible diffuse reflectance spectra and Brunauer-Emmett-Teller method were applied for measuring the light absorption capability and specific surface area of the synthesized heterostructured photocatalysts, respectively. In addition, photoelectrochemical measurements were conducted to study the photocurrent and resistance. Importantly, fluorescent lifetime decay curves were determined to better understand the possible charge transfer mechanisms at the interfaces of the heterostructures. Firstly, a classic p-n junction heterostructure composed of BiOI nanodot decorated TiO2 nanorod assembled microflowers was built and used as a prototype to study the interfacial charge transfer mechanisms. Through a self-developed synthesizing strategy, BiOI was deposited onto the surface of TiO2 with ultra-small sizes (~ 3 nm). Organic dye (Rhodamine B, RhB) and phenol as model pollutants were employed to investigate the photocatalytic ability of the synthesized photocatalysts under different light sources. With the assistance of the fluorescent lifetime decay curve, for the first time, the presence of reaction site self-quenching effect was found within the photocatalytic system which is harmful to the overall photocatalytic performances. Moreover, such a self-quenching effect became much more severe along with the ascending decoration amount of BiOI. In the second part of the thesis, heterostructures composed of ZnO and BiOI were designed and synthesized, with the aim to explore the possible working mechanisms of charges carriers in a core-shell structure which was subjected to the epitaxial growth through the matched crystal lattice. This photocatalyst showed superior photodegradation ability towards bisphenol A, a common endocrine chemical, under visible light illumination. Nevertheless, the observed performance was found to be related to the coating amount of BiOI. The fluorescent lifetime decay curve further revealed that the excessive coating amount of BiOI could inversely affect the charge transport in BiOI, with reduced effective charges at the interface of BiOI and ZnO. Based on the results obtained from the first two parts of the study, the possible charge transfer within the interface of a heterostructure was further studied in a photoelectrocatalytic system. With CoOx nanoclusters decorated TiO2 nanorod film as a prototype, the influence of morphology evolution on the charge transfer mechanism and the overall photoelectrocatalytic performance within a heterostructure were investigated, as the interface would vary with the combined form of the two components. Together with the fluorescent lifetime curve, for the first time, the (Foster-resonance energy transfer) FRET-assisted nanosensitizer re-excitation process was observed in nano-regional heterostructures, which was expected to compensate for the efficiency loss resulting from the oversized CoOx clusters. It is expected that this work could offer new insights into the rational design of high-performance functional heterostructures in the fields of photocatalysis and photovoltaics.